Implementasi The 70:20:10 Model Untuk Meningkatkan Spatial Literacy Skills Siswa Pada Mata Pelajaran IPS Terpadu di SMPN 5 Jonggat - Rahmania, Tri; Junaidin, Junaidin; Mas'ad, Mas'ad; Sanisah, Siti; Arif, Arif (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to assess the effectiveness of the 70:20:10 teaching model in improving students' spatial literacy skills in geography. This research applied the Classroom Action Research (PTK) approach implemented in two cycles at SMP Negeri 5 Jonggat with a focus on students in class VII IPS. The 70:20:10 model combines experiential learning (70%), social learning (20%), and formal learning (10%). Data were obtained through observations, interviews, and spatial literacy tests, which were then analyzed both quantitatively and qualitatively. The findings showed an increase in the average score from 45.39 (pre-cycle) to 62.87 (cycle I) and 75.24 (cycle II). The model proved effective in developing spatial skills through an active, collaborative and reflective approach. Therefore, the 70:20:10 model is a relevant teaching strategy to improve spatial literacy competencies and geography learning in the 21st era.